New method for measuring magnetoelectric effect in pulsed magnetic fields - Bueno-Baques, E.D.; Matutes-Aquino, J.; Corral-Flores, V.; Botello-Zubiate, M.; Rios-Jara, D.; Grossinger, R. (Functional Materials, 2006)
A new measurement method for magnetoelectric effect in pulsed magnetic fields has been developed. The pulsed field system generates in a bore of 25 mm fields up to 10.0 T with a typical pulse duration of 20 ms. Besides the magnetization, the system allows the measurement of the magnetoelectric effect in both transversal and longitudinal modes. The magnetoelectric effect on well known cobalt ferrite/ barium titanate composites and single-phase materials was measured as a function of the temperature. A maximum magnetoelectric coefficient of 1.5 mV/(cm•Oe) was obtained for a composite with a composition of 50 mass % ferrite sintered at 1200 °C. A model to explain the results obtained by this measurement method is discussed. Разработан новый метод измерения магнитоэлектрического эффекта в импульсных магнитных полях. Система импульсного поля генерирует в 25-мм отверстии поля до 10,0 Т с типичной длительностью импульса 10 мс. Помимо намагничивания, система позволяет измерять магнитоэлектрический эффект как в поперечном, так и в продольном направлениях. Измерен магнитоэлектрический эффект для хорошо известных композитов феррит кобальта/титаната бария и для однофазных материалов в зависимости от температуры. Максимальный магнитоэлектрический коэффициент 1.5 mV/(cm•Ое) получен для композита, содержащего 50% мас. феррита, спеченного при 1200 °С. Предложена модель для объяснения результатов, полученных описанным методом. Розроблено новий метод вимірювання магнітоелектричного ефекту в імпульсних магнітних полях. Система імпульсного поля генерує у 25-мм отворі поля до 10,0 Т з типовою тривалістю імпульсу 10 мс. Окрім намагнічування, система дозволяє вимірювати магнітоелектричний ефект як у поперечному, так і у поздовженьому напрямках. Виміряно магнітоелектричний ефект для добре відомих композитів ферит кобальту/титанат барію та для однофазних матеріалів в залежності від температури. Максимальний магнітоелектричний коефіцієнт 1,5 мВ/(см•Е) одержано для композиту, що містить 50 мас % фериту, спеченого при 1200 °С. Запропоновано модель для пояснення результатів, одержаних згаданим методом.